Kajian Sosiologis Hukum Pola Hubungan Perjanjian Terapeutik - Pakendek, Adriana; Purwandi, Agustri; Wardani, Win Yuli; Royana, Dila; Saputri, Arimurtika Fajariyah (Neolectura, 2023)
This study examines the therapeutic agreement relationship between doctors and patients within the context of healthcare services from the perspective of legal sociology and applicable regulations. Health, as a fundamental right guaranteed by the Indonesian Constitution, requires a supporting legal framework, as regulated in Law No. 17 of 2023 on Health. The therapeutic relationship, built on a mutual agreement between therapists and patients, is strengthened by factors such as trust, empathy, and openness, affecting the effectiveness of therapy. This research employs a normative legal method to elucidate existing legal issues, identify gaps between legal theory and practice, and propose solutions. The results indicate the importance of a deep understanding of social interaction in a legal context and the significant role of law in ensuring the application of ethical and responsible medical practices. This research aims to enhance patient awareness of their rights, expand the understanding of doctors and healthcare professionals about their professional obligations, and assist hospitals in improving service quality and reducing litigation risks.